Bridging spatially segregated redox zones with a microbial electrochemical snorkel triggers biogeochemical cycles in oil-contaminated River Tyne (UK) sediments. (15th December 2017) - Viggi, Carolina Cruz; Matturro, Bruna; Frascadore, Emanuela; Insogna, Susanna; Mezzi, Alessio; Kaciulis, Saulius; Sherry, Angela; Mejeha, Obioma K.; Head, Ian M.; Vaiopoulou, Eleni; Rabaey, Korneel; Rossetti, Simona; et al.
Abstract: Marine sediments represent an important sink for a number of anthropogenic organic contaminants, including petroleum hydrocarbons following an accidental oil spill. Degradation of these compounds largely depends on the activity of sedimentary microbial communities linked to biogeochemical cycles, in which abundant elements such as iron and sulfur are shuttled between their oxidized and reduced forms. Here we show that introduction of a small electrically conductive graphite rod ("the electrochemical snorkel") into an oil-contaminated River Tyne (UK) sediment, so as to create an electrochemical connection between the anoxic contaminated sediment and the oxygenated overlying water, has a large impact on the rate of metabolic reactions taking place in the bulk sediment. The electrochemical snorkel accelerated sulfate reduction processes driven by organic contaminant oxidation and suppressed competitive methane-producing reactions. The application of a comprehensive suite of chemical, spectroscopic, biomolecular and thermodynamic analyses suggested that the snorkel served as a scavenger of toxic sulfide via a redox interaction with the iron cycle. Taken as a whole, the results of this work highlight a new strategy for controlling biological processes, such as bioremediation, through the manipulation of the electron flows in contaminated sediments. Graphical abstract: Highlights: The snorkel enhances oil-fuelled sulfate reduction and suppresses methanogenesis. The snorkel interacts with sulfur and iron cycles occurring in the sediment. Poorly soluble Fe(III) species accumulate over the surface of the snorkel.